Pengaturan Badan Pengawas Pemilihan Umum terhadap Netralitas Aparatur Sipil Negara pada Pemilihan Kepala Daerah Kabupaten Ngada Tahun 2020 - Jessica Patricia Yustin Marthinus; Kotan Y. Stefanus; Hernimus Ratu Udju (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
According to the above article, it is in line with the regulations that the Regional Head Election is a democratic festivity, but there are several parties that are not allowed to be directly involved. One of them is the Civil Servants (ASN). ASN are state servants in the process of governance. Therefore, ASN are given limitations to remain neutral during this democratic festivity. However, they often face interference or are tainted by the involvement of ASN who should maintain their neutrality as government officials. The main issues in this research are (1) How is the regulation of the General Election Supervisory Agency on the neutrality of Civil Servants in the 2020 Regional Head Election in Ngada Regency? (2) What are the factors causing the neutrality violations of Civil Servants in the 2020 Regional Head Election in Ngada Regency? This research is empirical juridical research based on applicable laws and regulations and data obtained from the field. This research uses respondents and data collected in a descriptive qualitative manner. The aim of this research is to analyze the neutrality of Civil Servants (ASN) in the 2020 Regional Head Election (Pilkada) in Ngada Regency. The focus of the research is on how the regulation by the General Election Supervisory Agency (Bawaslu) affects the neutrality of ASN and the factors that cause neutrality violations. This research uses an empirical juridical method based on applicable laws and regulations as well as field data. Data were collected through semi-structured interviews with 10 respondents, including the Chairperson of Bawaslu, former coordinator of the violation dispute handling division, staff of the violation handling division, and ASN. Additionally, observation and documentation were used to complement the data. The research findings indicate that ASN neutrality violations often occur due to various factors, including political interference and the utilization of bureaucracy for Pilkada interests. This research provides recommendations to enhance supervision and law enforcement by Bawaslu to ensure ASN neutrality in every regional head election process in Indonesia.